Vegan is love : having heart and taking action - Roth, Ruby (North Atlantic Books, 2011)
Outlines what can be done to protect animals and the environment by making such decisions as refusing products tested on or made from animals, avoiding aquariums and zoos, and choosing to buy organic food.